Cooperative transmission for meter data collection in smart grid - Niyato, Dusit (2013)
Smart grid will become the next-generation electrical power system to provide reliable, efficient, secure, and cost-effective energy generation, distribution, and consumption. To achieve these goals, communications infrastructure and wireless networking will play an important role in supporting data transfer and information exchange in smart grid. In this article, the application of cooperative transmission for the meter data collection in smart grid is introduced. In a service area of smart grid, there are multiple communities composed of power consumption nodes (e.g., houses). The power consumption demand from the nodes is measured by a smart meter and transmitted to a meter data management system (MDMS) through the data aggregator unit (DAU) using wireless broadband access. The community invests in and deploys a relay station to perform relay transmission to improve the transmission rate and avoid congestion at the DAU. As a result, the MDMS will have complete and correct power demand data, which can be used to make better decisions on power supply. Since the communities in a service area of smart grid are rational, they will optimize the relay transmission strategy so that the total cost (i.e., power cost and transmission cost) is minimized. To analyze the relay transmission strategy of the community, the noncooperative game model is formulated, and the Nash equilibrium is considered as the solution. The proposed network architecture and analysis will be useful for the design and optimization of a wireless network for smart grid.